1977
DOI: 10.1093/ajcp/67.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Patterns (Antibiograms) as an Aid in Differentiating Citrobacter Species

Abstract: The hydrogen sulfide-negative Citrobacter group represents a taxonomic problem. Various investigators have proposed such designations as Padlewskia, Levinea, atypical Enterobacter cloacae, H2S-negative variants of Citrobacter, Citrobacter koseri and Citrobacter diversus. This problem has been investigated with emphasis on antibiograms as a means of discrimination. Clinical isolates fitting the designation Citrobacter were studied and, using the criteria of Ewing and Davis, separated into two groups: C. diversu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Holmes et al (1974) and Southern & Bagby (1977) reported that most strains of C. koseri were resistant to ampicillin and sensitive to cephaloridine and suggested that drug resistance was valuable in distinguishing between C. koseri and C. freundii. In the present study, however, 380 of strains were resistant to cephaloridine.…”
Section: Discussionmentioning
confidence: 99%
“…Holmes et al (1974) and Southern & Bagby (1977) reported that most strains of C. koseri were resistant to ampicillin and sensitive to cephaloridine and suggested that drug resistance was valuable in distinguishing between C. koseri and C. freundii. In the present study, however, 380 of strains were resistant to cephaloridine.…”
Section: Discussionmentioning
confidence: 99%
“…However, only experimental and in silico serotyping systems for Citrobacter detection have been developed to manage infections caused by it (Qian et al, 2018). It has been proposed that the affinity of C. koseri for nerve tissues and its propensity to induce meningitis and abscesses were related to a unique 32 kilodalton (kDa) outermembrane protein (Southern and Bagby, 1977;Kline et al, 1988;Li et al, 1990).…”
Section: Pathogenesismentioning
confidence: 99%